Environmental changes on the west coast of the Gulf of Thailand during the 8.2 ka event. (20th January 2020) - Chabangborn, Akkaneewut; Punwong, Paramita; Phountong, Karn; Nudnara, Worakamon; Yoojam, Noppadon; Sainakum, Assuma; Won-In, Krit; Sompongchaiyakul, Penjai
Abstract: The expression of the abrupt cooling of the 8.2 ka event in the tropics is poorly understood. In this study, we applied lithostratigraphy, loss on ignition, grain size and pollen analyses to sedimentary sequences from Thale Noi, which is located in the west coast of the Gulf of Thailand, in order to reconstruct the regional environmental history during the 8.2 ka event. Our results, based on sediment. This characteristics and pollen records, indicated that the study area was likely to have flooded prior to c. 8300 cal. a BP. The fall in sea-level coincided with a high precipitation, inferred from grain size, between c. 8250 and 8100 cal a BP. The increased precipitation can be attributed to the strengthening of the northeast (winter) monsoonal rains in the western Gulf of Thailand. The timing of the sea-level fall and strengthen stronger winter monsoon is consistent with the abrupt decrease in the temperature records emanating from the northern hemisphere. Subsequently, we observed a sea-level rise from c. 8100 to 7950 cal a BP, which potentially continued till c. 7650 cal. a BP. The possibility of coastal erosion was detected by a hiatus in the sedimentary sequences dated between c. 7950 and 7650 cal a BP. Then, a standstill of the sea-level occurred from c. 7650 to 7100 cal a BP. This transgression is suggested to have caused coastal erosion that resulted in a hiatus in the sedimentation process between c. 7950 and 7650 cal a BP. Correspondingly, fluctuations in the monsoon strength resulted in an overall decreased precipitation from c. 8100 to 7450 cal a BP, although punctuated wet intervals were observed at c. 7950 and 7575 cal a BP. Highlights: This research is focused on the past environmental changes on the west coast of the Gulf of Thailand during the 8.2 ka event. The study area has been consider to be tectonic stable and under tropical climate. These assumptions allow us to separate the tectonic adjustment and glacial isostatic from the eustatic change. Moreover, it is located in the boundary of the Asian monsoon subsystems. The archives from this area therefore can potential record the monsoon variability. The chronology of the sediment sequence is based on 9 14C dates spaning from 8300 to 7200 cal. a BP. This high resolution of dating results allows us to follow the abrupt environmental change during the 8.2 ka event.